Tinjauan Viktimologi terhadap Korban Kekerasan Seksual yang Rentan Hak dan Perlindungan Hukumnya (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
The protection of victims of sexual violence in Indonesia's national legal system is representative of the state's commitment to uphold human dignity, as mandated by the constitution. The constitutional basis for this protection is stated in the 1945 Constitution of the Republic of Indonesia, especially Article 28G paragraph (1), which states that everyone has the right to protection of privacy, honor, dignity, and freedom from treatment that degrades human values. Currently, sexual violence can occur anywhere, especially in the scope of education. The impact of sexual violence causes a lot of harm to its victims, from the impact on the victim's psychology to the physical impact. The purpose of the research is related to the effectiveness of law enforcement or the operation of the law and the background of the law. Whether a legal protection can protect the rights of victims of sexual violence, and provide proper protection that must be obtained for victims of sexual violence. This research uses emprical research methods and a case approach which is used to analyze the handling of cases of “Sexual Violence and Forced Abortion” as a real form of legal application. With the existence of legal protection for victims of sexual violence provided by the state, it does not guarantee victims get the promised justice. Social stigma is one that can exacerbate the suffering of victims, making them isolated and reluctant to seek help. Society often tends to blame the victim, creating an unsupportive and even demeaning environment. Therefore, it is important to address social stigma in the context of sexual violence to impact the well-being of the individual as well as society as a whole.